Activity of organic acid salts in combination with lauric arginate against Listeria monocytogenes and Salmonella Rissen - Suchart Suksathit; Pussadee Tangwatcharin (My University, 2013)
The objective of this study was to investigate the in vitro activities of sodium diacetate (SD), sodium citrate (SC), or sodium lactate (SL) in combination with lauric arginate (LAE) against Listeria monocytogenes and Salmonella Rissen.Bacteria isolated from a pig carcass were used to determine the minimum inhibitory and bactericidal concentrations (MIC and MBC), fractional bactericidal concentration index (FBCI), time-kill method, as well as to perform scanning and transmission electron microscopy characterizations.For L. monocytogenes, the MBC of SD, SC, LAE and SL were 62.5, 62.5, 0.032 mg/ml, and 8.4% (v/v), respectively.As for S. Rissen, the MBC of SD and LAE were 62.5 and 0.032 mg/ml, respectively.The effects of SD, SC, and SL in combination with LAE were synergistic against both bacteria, exhibiting FBCIs of 0.19, 0.50, and 0.50, respectively, for L. monocytogenes and 0.19, 0.50 and 0.50, respectively, for S. Rissen.In time-kill studies, all salts of organic acids plus LAE combinations added at their MBC produced a bactericidal effect that was dependent on the type of bacteria and antimicrobial.This resulted in a loss and change of the cytoplasm and membrane in cells of both bacteria.Furthermore, SC and SL alone were not active in killing S. Rissen.The present investigation revealed that salts of organic acid in combination with LAE are potentially antilisterial and anti-salmonella agents, which can be applied to meat products.
Keywords: Coconut Research and Applications